Post-Streptococcal Uveitis: a Rare Entity - Rossi, D. C.; Sadeghi, Y.; Di Lucca, J.; Maitre, S.; Hofer, M.; Guex-Crosier, Y. (Klinische Monatsblätter für Augenheilkunde, 2017)
Without appropriate treatment, Group A streptococcal infections can lead to post-streptococcal syndrome, including post-streptococcal uveitis. This should be kept in mind in young patients with acute bilateral non-granulomatous anterior uveitis, in order to avoid ocular and systemic complications. We report two cases of bilateral post-streptococcal anterior uveitis, in young men, of respectively 20 and 16 years old, that presented to Jules Gonin Eye Hospital.
Keywords: post-streptococcal uveitis; PSU; antistreptolysin-O titres; ASOT